Influence of trace elements changes in the cerebellum on the rat's behavior in elevated plus maze in the early period of mild blast-induced traumatic brain injury - Yu. V. Kozlova (Zaporozhye State Medical University, 2024)
The aim of the current study was to determine whether there are changes in brain trace elements of rats with blast-induced trauma and if these changes affect behavior in the elevated plus maze. Materials and methods. The study was carried out on 126 sexually mature male Wistar and were divided into 3 groups: Experimental - exposed to a shock wave 26.4 ± 3.6 kPa (n = 42); Sham (n = 42), the animals of which were subjected to inhalation anesthesia with halothane and fixation in a horizontal position; and Intact (n = 42). Behavior was study in elevated plus maze. The duration of presence in the open and closed arms, the number of stands, the duration of grooming was recorded in all groups of rats for 3 minutes. After, the animals were euthanized with halothane, followed by removal of the brain. The cerebellum was completely separated for spectral analysis using energy dispersive X-ray fluorescence analysis (EDRFA) on the analyzer EXPERT 3 XL. Results. Results showed significant changes of cognitive activity in experimental group which are indicate functional disorders of the cerebellum in the form of maladaptation in space with subsequent inhibition of motor centers. Cu/Fe ratio was decreased in the 14th and 21st days and increased in the 28th. Cu/Zn ratio was decreased on the 14th day. Zn/Fe ratio was higher on the 14th and 28th days. The existence of correlations between changes in trace elements and behavioral disorders in experimental rats was established. Conclusions. In the early period of blast-induced traumatic brain injury, cerebellar dysfunction in the form of spatial maladaptation with subsequent depression of motor centers was observed in the experimental rats Correlation analysis showed the presence of different strengths and directions of relationships between the ratios of Cu/Fe, Cu/Zn and Zn/Fe in the cerebellum and behavioral indicators in the elevated plus maze (duration of stay in open and closed arms, grooming and vertical motor activity) of experimental rats.